Brief Report: High HIV Incidence in a South African Community of Men Who Have Sex With Men. (15th December 2016) - Lane, Tim; Osmand, Thomas; Marr, Alexander; Struthers, Helen; McIntyre, James A.; Shade, Starley B.
Abstract : Abstract: Cross-sectional studies among African men who have sex with men (MSM) populations demonstrate high HIV prevalence, but few incidence estimates exist. The Mpumalanga Men's Study in Gert Sibande, Mpumalanga province, South Africa, involved 3 serial cross-sectional surveys of MSM recruited through respondent-driven sampling between 2012 and 2015. Successive surveys recaptured a nested cohort of 179, contributing 144.3 person-years (PY) of observation. We observed 18 seroconversions, or incidence of 12.5/100 (PY) (95% confidence interval CI: 8.1 to 19.2/100 PY). Presumptions of high incidence among MSM were confirmed and demonstrate an urgent need for biomedical prevention and treatment programming for MSM in South Africa.